MEASURING LISTENING SKILLS THROUGH STRATEGY TO NOTE (NOTETAKING) ON KEYWORDS AT SMK N 1 PEMATANGSIANTAR - Gultom, David Gordon; Hutasoit, Patri; Sirait, Salomo Parsaulian (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aims to determine the role of note taking strategies on listening skills (listening). The research method used in this study is a True research method Experimental Design whose implementation uses the Posttest-Only Control Design type compares the experimental class with the control class. At SMK N 1 PEMATANGSIANTAR, the population of all students in class XI Program Mechanical Engineering Expertise. Samples were taken as many as 52 with a random class technique sampling. The instruments used are MGMP questions and UN questions (Listening). From data processing the results obtained: there are differences in listening learning achievement between before and after using note-taking strategy.